2004
DOI: 10.1117/12.530023
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of kink characteristic of proton-implanted VCSEL with ITO overcoating

Abstract: Proton implanted VCSEL has been demonstrated with good reliability and decent modulation speed up to 1.25 Gb/s. However, kinks in current vs light output (L-I) has been always an issue in the gain-guided proton implant VCSEL.The kink related jitter and noise performance made it difficult to meet 2.5 Gb/s (OC-48) requirement. The kinks in L-I curve can be attributed to non-uniform carrier distribution induced non-uniform gain distribution within emission area. In this paper, the effects of a Ti/ITO transparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The output power depends strongly on the aperture size [1][2][3]. Generally, there are two ways to fabricate the isolated current apertures; oxideconfinement or ion implantation [4]. Since D. L. Huffaker et al reported the VCSELs fabricated using a stable native oxidation [5], the major technique has been oxideconfinement, and a great number of studies on oxide-confined VCSELs have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The output power depends strongly on the aperture size [1][2][3]. Generally, there are two ways to fabricate the isolated current apertures; oxideconfinement or ion implantation [4]. Since D. L. Huffaker et al reported the VCSELs fabricated using a stable native oxidation [5], the major technique has been oxideconfinement, and a great number of studies on oxide-confined VCSELs have been reported.…”
Section: Introductionmentioning
confidence: 99%